Theory of Mind and Its Neuropsychological and Quality of Life Correlates in the Early Stages of Amyotrophic Lateral Sclerosis - Trojsi, Francesca; Siciliano, Mattia; Russo, Antonio; Passaniti, Carla; Femiano, Cinzia; Ferrantino, Teresa; De Liguoro, Stefania; Lavorgna, Luigi; Monsurrò, Maria R.; Tedeschi, Gioacchino; Santangelo, Gabriella (Frontiers in Psychology, 2016)
This study aims to explore the potential impairment of Theory of Mind (ToM) (i.e., the ability to represent cognitive and affective mental states to both self and others) and the clinical, neuropsychological and Quality of Life (QoL) correlates of these cognitive abnormalities in the early stages of amyotrophic lateral sclerosis (ALS), a multisystem neurodegenerative disease recently recognized as a part of the same clinical and pathological spectrum of frontotemporal lobar degeneration. Twenty-two consecutive, cognitively intact ALS patients, and 15 healthy controls, underwent assessment of executive, verbal comprehension, visuospatial, behavioural and QoL measures, as well as of the ToM abilities by Emotion Attribution Task (EAT), Advanced Test of ToM (ATT) and Eyes Task (ET). ALS patients obtained significantly lower scores than controls on EAT and ET. No significant difference was found between the two groups on ATT. As regard to type of ALS onset, patients with bulbar onset performed worse than those with spinal onset on ET. Correlation analysis revealed that EAT and ET were positively correlated with education, memory prose, visuo-spatial performances and “Mental Health” scores among QoL items. Our results suggest that not only “cognitive” but also “affective” subcomponents of ToM may be impaired in the early stages of ALS, with significant linkage to disease onset and dysfunctions of less executively demanding conditions, causing potential impact on patients' “Mental Health”.